Income and structural convergence of Western Balkans to European Union - Ermelinda Meksi; Ermelinda Xhaja (Gjika) (The European Journal of Comparative Economics, 2017)
This paper aims to model the convergence of economic development of Albania within the Western Balkans and in the context of European integration aspirations of the region. The conclusion of this paper is that the Balkan countries have converged among themselves and toward European Union (EU). But the speed of the convergence is moderated with the hit of global crisis and the recovery still seems difficult to the rate of pre-crisis. As economies in transition that are attempting to converge with the European development stages, the economies of the Balkan countries have to go through structural evolutions that are similar among countries. The variables used in this study are the income per capita, growth rate, sector contribution to GDP growth and the added value per worker in agriculture. The data is measured for the period from 1995 to 2015 in order to establish a substantial data series for trend analysis and understanding if countries in the study are converging or diverging with EU in terms of their income and economies profile. The issue of the productivity and further specialization of their output by using their advantages in resources comes into question.